Understanding resistance to reductions in water subsidies in Kuwait. Issue 1 (2nd January 2022) - Aljamal, Ali; Speece, Mark; Bagnied, Mohsen
ABSTRACT: Sustainability in Kuwait requires more realistic pricing for currently highly subsidised water, to discourage wasteful usage. There is, however, strong public resistance to eliminating water subsidies. This research explores reasons for this consumer resistance, using qualitative in-depth interviews. The issues in this affluent society are not really about economics at all, but stem from perceptions about government responsibility to citizens, fairness, and weak top-of-mind awareness of environmental/sustainability issues when actually using water. When considering the issues more carefully, there is substantial willingness to pay for tap water with policies perceived as fair, supported by an effective communications campaign. Policy-makers can use such data to develop a comprehensive water pricing campaign that will minimise political resistance and contribute to a much more sustainable urban water management.